Mesopotamia - Schwemer, Daniel (Guide to the study of ancient magic, 2019)
This chapter surveys forms of ritual considered dangerous or potentially harmful in ancient Mesopotamia. It first delineates the wider context of ritual lore in Babylonia and Assyria, focussing in particular on the profession of the āšipu. It then describes the ideas and concepts associated with kišpū, the Akkadian term for malevolent and taboo ritual acts, and includes a discussion of the stereotypical female perpetrator of kišpū. Finally, it examines ambiguity in these ritual practices and the concept of “evil” ritual as a cultural narrative in the context of the first-millennium Mesopotamia.